2019
DOI: 10.1016/j.omtn.2019.08.018
|View full text |Cite
|
Sign up to set email alerts
|

Crosstalk of mRNA, miRNA, lncRNA, and circRNA and Their Regulatory Pattern in Pulmonary Fibrosis

Abstract: Noncoding RNAs (ncRNAs), such as microRNA (miRNA), long ncRNA (lncRNA), and circular RNA (circRNA), are regulators of important biological functions. Therefore, understanding their crosstalk and regulatory patterns can provide treatment for diseases. In this study, differentially expressed RNA transcripts were obtained by RNA sequencing in bleomycin-induced pulmonary fibrosis in mice. Four miRNAs, 10 lncRNAs, and two circRNAs were tested to validate the sequencing. There were differentially expressed 585 mRNAs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
63
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 81 publications
(63 citation statements)
references
References 43 publications
0
63
0
Order By: Relevance
“…In intervertebral disc degeneration, multiple competitive endogenous RNA (ceRNA) networks were obtained, such as the lncRNA metastasis-associated lung adenocarcinoma transcript 1 (MALAT1)/circRNA_102348/miR-185-5p/transforming growth factor-beta 1 (TGFB1) axis, the circRNA_102399/miR-302a-3p/hypoxia-inducible factor 1 subunit alpha (HIF1A) axis, and the circRNA_100086/miR-509-3p/ mitogen-activated protein kinase 1 (MAPK1) axis, etc 16 . In pulmonary fibrosis, circRNA_949 (chromosome 14: 30346797-30350949) and circRNA_057 (chromosome 6:99003199-99100057) form a regulatory network with lncRNA NONMMUT039865 and lncRNA NONMMUT039556, simultaneously regulating miR-29b-2-5p targeting signal transducer and activator of transcription 3 (STAT3) phosphorylation in a bleomycin-induced mouse model 17 .…”
Section: Introductionmentioning
confidence: 99%
“…In intervertebral disc degeneration, multiple competitive endogenous RNA (ceRNA) networks were obtained, such as the lncRNA metastasis-associated lung adenocarcinoma transcript 1 (MALAT1)/circRNA_102348/miR-185-5p/transforming growth factor-beta 1 (TGFB1) axis, the circRNA_102399/miR-302a-3p/hypoxia-inducible factor 1 subunit alpha (HIF1A) axis, and the circRNA_100086/miR-509-3p/ mitogen-activated protein kinase 1 (MAPK1) axis, etc 16 . In pulmonary fibrosis, circRNA_949 (chromosome 14: 30346797-30350949) and circRNA_057 (chromosome 6:99003199-99100057) form a regulatory network with lncRNA NONMMUT039865 and lncRNA NONMMUT039556, simultaneously regulating miR-29b-2-5p targeting signal transducer and activator of transcription 3 (STAT3) phosphorylation in a bleomycin-induced mouse model 17 .…”
Section: Introductionmentioning
confidence: 99%
“…LncRNA-NONMMUT028949.2 (lnc949) has a remarkably high expression in pulmonary fibrosis according to our previous study (Li et al. 2019 ). Thus, lnc949 was chosen to further identify the lncRNA regulation of engeletin during its drug action.…”
Section: Resultsmentioning
confidence: 59%
“…Lnc949-mediated TGF-b1-Smad2/3 and JNK were the upstream signalling pathways of ER stress induced by engeletin Long noncoding RNA (lncRNA) is a class of noncoding gene that regulates protein-coding genes in their upstream signalling pathways. LncRNA-NONMMUT028949.2 (lnc949) has a remarkably high expression in pulmonary fibrosis according to our previous study (Li et al 2019). Thus, lnc949 was chosen to further identify the lncRNA regulation of engeletin during its drug action.…”
Section: Regulation Of Engeletin In Pulmonary Fibrosis-associated Sigmentioning
confidence: 99%
“…For instance, cir-ITCH acts as a tumor suppressor in esophageal squamous cell carcinoma via sponging miR-7, miR-17, and miR-214 (Li F. et al, 2015). In addition, circRNAs have been reported to be involved in the progression of fibrotic diseases such as cardiac fibrosis and pulmonary fibrosis (Li et al, 2019;Gu et al, 2020). Herein, we found that cMTO1 participated in the progression of liver fibrosis.…”
Section: Discussionmentioning
confidence: 75%